Industrial education - Forsythe, George (My University, 1895)
Introduction: It is truly said, we live in a progressive age, progressive not only in religion, science, and art, but the whole universe screams to be pushing forward at a break-neck speed. As the natural forces are working for the first place in the universe, so is man striving for the brightest places in society and in the acquirement of wealth.
Citation: Forsythe, George. Industrial education. Senior thesis, Kansas State Agricultural College, 1895.
Morse Department of Special Collections
Keywords: Progressive age; Religion; Science; Art; Society; Wealth; Theses; Manuscripts (documents)